ANALISIS PERMAINAN TRADISIONAL TERHADAP PERKEMBANGAN KETERAMPILAN FISIK MOTORIK ANAK KELAS 1 SEKOLAH DASAR JABAL NUR - FATMAWATI . (JURNAL ILMIAH MAKSITEK, 2020)
This research aims to: (1) Analyze traditional games; (2) Analyze the physical development of the child's motor; Theresearch was conducted at jabal nur tebing tinggi integrated Islamic elementary school. The subjects in the study wereprincipals, teachers and children at jabal nur integrated Islamic elementary school. As for the collection of data in this studythrough observations, interviews and documentation. Meanwhile, data analysis using miles and huberman models is datareduction, data presentation and conclusion drawing. The results showed that: (1) traditional games such as clogs are ableto provide good stimulation to the motor physical development of elementary school year 1 children; (2) Teachers uselearning methods by playing and introducing traditional games capable of giving students attractiveness in learning, thusachieving learning goals. Based on observations, interviews, the physical development of children's motor is achieved byusing traditional games as a learning transfer tool.